The android-based instrument for performance assessment of football - I Wayan Artanayasa; Ketut Chandra Adinata Kusuma; I Made Satyawan; Hendra Mashuri (Jurnal Cakrawala Pendidikan, 2023)
The android-based performance assessment instrument in football learning is the result of the development of a football learning assessment instrument that adapts to the digital era. This study aims to test the validity and practicality of an android-based performance assessment instrument in football learning. The research method used was a validation test by media and soccer material experts and a practicality test by a football course lecturer. Application testing is carried out based on predetermined criteria. After being assessed by the validator and meeting the valid criteria, this application is then tested (implemented) by the subject or user. The data collection instruments used were field notes, expert validation sheets, and questionnaires. The media feasibility test of the assessment referred to the User Experience Questionnaire (UEQ) standard. Data analysis was conducted to determine the applicant's eligibility and validity category based on the assessments of media experts and soccer learning evaluation experts. The results showed that the developed application was acceptable, with an average score of 3.67 from media experts and 3.83 from material experts so the total average of the expert test is 3.75 with very valid criteria. The product developed is an application of an android-based performance instrument for soccer learning that follows the assessment rubric in the PJOK curriculum and is practically used by PJOK educators as an evaluation tool for PJOK football material.